FIBROMYALGIA IN EARLY OSTEOARTHRITIS; A TERTIARY CARE HOSPITAL EXPERIENCE - Hussain, Ibrar; Mustafa, Syed Hassan; Adnan, Saqib; Khan, Suleman; Ullah, Naeem; Hayat, Waqar (Journal of Postgraduate Medical Institute, 2022)
Objectives: To find the prevalence of fibromyalgia in patients with early knee osteoarthritis. Methodology: In this observational cross-sectional study 115 patients (age 18-49) in which 65 females and 50 males were selected from the Department of Rheumatology, Lady Reading Hospital Peshawar from August 2020 and February 2021. The American College of Rheumatology 1990 criteria and American Classification Criteria 1986 were used for the diagnosis of fibromyalgia in early knee osteoarthritis. Results: Mean age of the patients was 37.38 ± 9.14 years. There were 50 patients (females= 38, males = 12) who reported fibromyalgia. Moreover, there were 41 patients with hypertension, 3 with diabetes, and 1 with ischemic heart disease. Similarly, 3 patients reported hypothyroidism while 1 patient-reported chronic kidney disease. As regards fibromyalgia, 50 patients with early OA were found to have fibromyalgia comprising 43.5% of the total patients. Conclusion: It is concluded that fibromyalgia is a commonly occurring disease among patients with early knee osteoarthritis. This condition affects both sexes, although females are far more likely to develop fibromyalgia as compared to males. The results of this study further highlighted the need for awareness, early diagnosis, and timely management of Fibromyalgia preventing patients from being over-treated for early knee OA.